Combined numerical and experimental investigation of the micro-hydrodynamics of chevron-based textured patterns influencing conjunctional friction of sliding contacts. (April 2015) - Morris, N; Leighton, M; De la Cruz, M; Rahmani, R; Rahnejat, H; Howell-Smith, S
Reciprocating and low-speed sliding contacts can experience increased friction because of solid boundary interactions. Use of surface texturing has been shown to mitigate undue boundary friction and improve energy efficiency. A combined numerical and experimental investigation is presented to ascertain the beneficial effect of pressure perturbation caused by micro-hydrodynamics of entrapped reservoirs of lubricant in cavities of textured forms as well as improved micro-wedge flow. The results show good agreement between numerical predictions and experimental measurements using a precision sliding rig with a floating bed-plate. Results show that the texture pattern and distribution can be optimised for given conditions, dependent on the intended application under laboratory conditions. The translation of the same into practical in-field applications must be carried out in conjunction with the cost of fabrication and perceived economic gain. This means that near optimal conditions may suffice for most application areas and in practice lesser benefits may accrue than that obtained under ideal laboratory conditions.